A Comparison of Nonopioid and Opioid Oral Analgesia following Pediatric Palatoplasty. (March 2017) - Pierson, Brandon W.; Cardon, Brandon S.; Anderson, Michael P.; Glade, Robert S.
Objective: This article evaluates postoperative analgesia in pediatric palatoplasty patients using nonopioid oral medications. Design: This study was a retrospective chart review. Setting: The setting for this study was a tertiary-care children's hospital. Participants: Study participants were pediatric patients who underwent palatoplasty procedures performed by a single surgeon. Interventions: Interventions included nonopioid and opioid oral medications for postoperative analgesia. Main Outcome Measures: The adequacy of nonopioid versus opioid oral analgesia was assessed by (1) time to discontinue IV fluid, (2) total IV morphine doses for breakthrough pain, (3) daily IV morphine doses for breakthrough pain, (4) time to discharge from the hospital, and (5) perioperative weight change. Group comparisons of outcome measures were performed using a two one-sided test. Results: A total of 61 patients were identified who received three standard pain regimens: acetaminophen + ibuprofen (12), hydrocodone/acetaminophen (23), and hydrocodone/acetaminophen + ibuprofen (26). There was sufficient evidence to suggest equivalence in outcome measures for acetaminophen + ibuprofen versus hydrocodone/acetaminophen and hydrocodone/acetaminophen + ibuprofen for the following: time to discontinue IV fluid ( P = .02, 90% confidence interval [CI] = –0.42 to 0.17; P = .007, 90% CI = –0.28 to 0.34), daily IV morphine doses ( P = .023, 90% [CI] = –0.83 to 0.65; P = .032, 90% [CI] = –0.92 to 0.28), time to discharge from the hospital ( P = .017, 90% [CI] = –0.40 to 0.27; P = .015, 90% [CI] = –0.24 to 0.39), and perioperative weight change ( P = .002; 90% CI = –0.25 to 0.46; P < .0001; 90% CI = –0.34 to 0.18). There was no sufficient evidence to suggest equivalence for total IV morphine doses ( P = .189, 90% CI = –1.51 to 1.78; P = .169, 90% CI = –1.51 to 0.88). Conclusions: Oral acetaminophen and ibuprofen alone may provide similar analgesia to traditional regimens with reduced risks following pediatric palatoplasty.